La Cité de l'Innovation et des Savoirs Aix-Marseille (CISAM): an inspiring value proposition for the African entrepreneurial university? - (:unkn) unknown (My University, 2024)
The structural and cultural challenges facing African universities, including political instability, social inequalities and lack of resources - and the mismatch between the skills acquired through their academic programs and the needs of the job market - are all problems that result in high graduate unemployment and a weak entrepreneurial culture. Hence the importance of strengthening synergies between universities and industry to foster innovation and economic development. The article presents an analysis of university entrepreneurship in Africa, focusing in particular on its training and support needs and the solutions deployed. It highlights the need for universities to play a proactive role in promoting innovation to meet current societal challenges. And, with this in mind, it analyzes the value proposition of the Cité de l'Innovation et des Savoirs Aix-Marseille (CISAM) as an inspiring model, focusing on training and support for entrepreneurship. The results show that CISAM can indeed inspire the African entrepreneurial university, both in terms of training, where it integrates prototyping skills, support, where it complements the incubation offer, and innovation, by facilitating applied research and technology transfer.
Keywords: African Research